Assessing the Minimum Sampling Effort Required to Reliably Monitor Wild Meat Trade in Urban Markets - Mayor, Pedro; El Bizri, Hani R.; Morcatty, Thais Q.; Moya, Kelly; Solis, Samantha; Bodmer, Richard E. (Frontiers in Ecology and Evolution, 2019)
The trade of wild meat has become a controversial topic because despite the economic returns it generates for local communities, it can cause a dramatic increase in harvest rates of game species. Monitoring wild meat trade in urban markets could be an accessible and low-cost method to assess the impacts on game populations. Nevertheless, this activity is difficult to monitor because it is illegal in most countries and vendors often distrust researchers. We used two long-term monitoring datasets collected in one of the most important and largest urban markets in wildlife in the Amazon, in Iquitos, Peru, to estimate the minimum effort required to obtain reliable information on the amount and price of wild meat. Two 12-month surveys were conducted in the Belén Market between September 2006 and August 2007 (2,443 interviews over 182 sampling days), and between September 2017 and August 2018 (2,081 interviews over 138 sampling days). To assess the reliability of different survey efforts, we modeled ten scenarios differing in sampling size and amount of meat traded, and calculated their accuracy and precision. In 2006-2007, sellers sold an average of 663.1 ± 188.7 kg per day at an average price of US$ 3.82 ± 0.19. In 2017-2018, sellers sold an average of 642.0 ± 248.3 kg per day at an average price of US$ 6.04 ± 0.33. Any sampling effort equal to or above two sampling days per month results in good accuracy (>90%) and precision (>85%), independently of the amount of wild meat sold. In addition, the vendors’ perception on the daily amount of meat sold was similar to the amount of wild meat on sale (accuracy = 98%), suggesting that sellers are aware of the amount of wild meat brought to the market. In contrast, vendors perceived that they sold 78% of the volume of wild meat compared to estimations obtained from our year-along surveys. We recommend that a minimum sampling effort of two interviews per month should be used to monitor wild meat trade in open urban markets; in other occasions, a punctual interview on meat sellers perception may also be useful.